Tracy - she broke his heart : the morning after Cyclone Tracy devastated Darwin, Casuarina resident Lynn John Cox returned from holidays to his wrecked home, 1974 - Howard, Bruce, 1936-; Herald and Weekly Times ([Melbourne] : Herald and Weekly Times, 1974)
"He was unsure of the fate of his wife and children. Thay had escaped and were sheltering at a local school hall."--File 204/09/00042.
Part of collection: Bruce Howard collection of photographs for Herald and Weekly Times, Melbourne, 1955-1995.
Title supplied by photographer, see acquisition file 204/09/00042.
Inscriptions: "Please return print to Bruce Howard." -- in ink on reverse.
Also available online
Keywords: Cyclones -- Northern Territory -- Darwin -- Photographs; Cyclone Tracy, 1974 -- Photographs; Natural disasters -- Northern Territory -- Darwin -- Photographs; Lost architecture -- Northern Territory -- Darwin -- Photographs